2015
DOI: 10.1002/pros.22998
|View full text |Cite
|
Sign up to set email alerts
|

Circulating total testosterone and PSA concentrations in a nationally representative sample of men without a diagnosis of prostate cancer

Abstract: Background The association between serum sex steroid hormones and PSA in a general population has not been described. Methods Included were 378 men aged 40-85 years who participated in the National Health and Nutrition Examination Survey in 2001-2004, who did not have a prostate cancer diagnosis, and had not had a recent biopsy, rectal examination, cystoscopy, or prostate infection or inflammation. Serum total PSA, total testosterone, androstanediol glucuronide (3α-diol-G), estradiol, and sex hormone binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
4
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 16 publications
(13 reference statements)
2
31
4
2
Order By: Relevance
“…If vitamin D is linked with higher PSA, which prompts prostate biopsies, then vitamin D would appear to be positively associated with prostate cancer risk without a causal influence on prostate cancer aetiology. The association between sex steroid hormones and PSA concentration (including a positive association between testosterone and PSA concentration) in continuous NHANES has been reported previously …”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…If vitamin D is linked with higher PSA, which prompts prostate biopsies, then vitamin D would appear to be positively associated with prostate cancer risk without a causal influence on prostate cancer aetiology. The association between sex steroid hormones and PSA concentration (including a positive association between testosterone and PSA concentration) in continuous NHANES has been reported previously …”
Section: Methodsmentioning
confidence: 68%
“…The association between sex steroid hormones and PSA concentration (including a positive association between testosterone and PSA concentration) in continuous NHANES has been reported previously. 17…”
Section: Study Populationmentioning
confidence: 99%
“…However, small increases in PSA levels in men initiating TTh during the first few months following therapy initiation have been observed [29]. Furthermore, a recent study observed overall higher PSA levels in men on T [25]. However, these increases in PSA levels are not related to the risk of CaP, and support the stimulation of prostate tissue containing unsaturated androgen receptors, as described in the prostate saturation theory proposed by Morgentaler [26].…”
Section: Discussionmentioning
confidence: 86%
“…As a result, low volume and low grade cancers associate with lower median levels of TT and PSA as well as high volume and high grade cancers associate with increased median levels of TT and PSA. The positive association between TT and PSA has also been demonstrated in men who did not have a diagnosis of PCA; indeed, men with higher testosterone had higher PSA [21] . Our upgrading risk model relates to the pathophysiology of the disease along the pituitary-testis-prostate axis and supports the positive functional relation between TT and PSA levels in PCA patients.…”
Section: Modelmentioning
confidence: 83%